Street Food as part of the Resistance-Fxistence: from 18th to 20th Century - Araújo Queiroz, Greiziene; de Souza Mendonça Menezes, Sônia (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The objective of this article is to relate street food to the concept of «Resistance-existence» (r-existence) The authors present a brief history of street food in the urban space of Bahia, Brazil.After this approach, local food is discussed as r-existence in the street cuisine of the cities of Ilhéus and Itabuna. Three elements of Bahian cuisine were chosen for analysis: papilla, acarajé, and cocada. The authors used bibliographic research and interviews with street food workers and consumers as a methodological resource. The concept of r-existence addresses the issue of street food insofar as workers remain on the street and resist the historical erasure of their activity. The r-existence in street food is due to the fact that this food is based on the identity of Bahian culture, resulting from the indigenous, African, and Portuguese contributions. This food preserves knowledge and practices passed down from generation to generation, which consolidates its r-existence, as it does not disappear over time but, rather, becomes stronger.